Malignancy in coeliac disease--effect of a gluten free diet. Issue 3 (March 1989) - Holmes, G K; Prior, P; Lane, M R; Pope, D; Allan, R N
Abstract : Two hundred and ten patients with coeliac disease previously reported from this unit were reviewed at the end of 1985 after a further 11 years of follow up. The initial review at the end of 1974 could not demonstrate that a gluten free diet (GFD) prevented these complications, probably because the time on diet was relatively short. The same series has therefore been kept under surveillance with the particular aim of assessing the effects of diet on malignancy after a further prolonged follow up period. Twelve new cancers have occurred: of which one was a carcinoma of the oesophagus and two lymphomas. Thirty nine cancers developed in 38 patients and of 69 deaths, 33 were the result of malignancy. A two-fold relative risk (RR) of cancer was found and was because of an increased risk of cancer of the mouth and pharynx (RR = 9.7, p less than 0.01, 95% confidence interval (CI) = 2.0-28.3), oesophagus (RR = 12.3, p less than 0.01, CI = 2.5-36.5), and of non-Hodgkin's lymphoma (RR = 42.7, p less than 0.001, CI = 19.6-81.4). The results indicate that for coeliac patients who have taken a GFD for five years or more the risk of developing cancer over all sites is not increased when compared with the general population. The risk is increased, however, in those taking a reduced gluten, or a normal diet, with an excess of cancers of the mouth, pharynx and oesophagus (RR = 22.7, p < 0.001), and also of lymphoma (RR = 77.8, p < 0.001). A significant decreasing trend in the excess morbidity rate over increasing use of a GFD was found. The results are suggestive of a protective role for a GFD against malignancy in coeliac disease and give further support for advising all patients to adhere to a strict GFD for life.